1996
DOI: 10.1523/jneurosci.16-09-03019.1996
|View full text |Cite
|
Sign up to set email alerts
|

Chronic 3-Nitropropionic Acid Treatment in Baboons Replicates the Cognitive and Motor Deficits of Huntington’s Disease

Abstract: We showed recently that chronic administration of the mitochondrial inhibitor 3-nitropropionic acid (3NP) in primates produces various dyskinetic movements and dystonic postures associated with selective striatal lesions displaying many similarities with the pathological features of Huntington's disease (HD). In the present study, we examined whether such a toxic treatment could also induce frontal-type deficits similar to those observed in HD patients. Cognitive performances of 3NP-treated and control baboons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
98
0
6

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 242 publications
(108 citation statements)
references
References 44 publications
4
98
0
6
Order By: Relevance
“…3-NP treatment significantly caused cognitive dysfunction as demonstrated by the results of MWMT (delayed transfer latency and decreased time spent in the target quadrant). These findings are in agreement with earlier reports suggesting a variety of neurobehavioral abnormalities and cognitive deficits after 3-NP administration (Kumar & Kumar, 2009b;Palfi et al, 1996). It has also been reported that 3-NP produces lesion in hippocampal CA1 and CA3 pyramidal neurons, areas of the brain associated with cognitive task (Sugino et al, 1999).…”
Section: Discussionsupporting
confidence: 93%
“…3-NP treatment significantly caused cognitive dysfunction as demonstrated by the results of MWMT (delayed transfer latency and decreased time spent in the target quadrant). These findings are in agreement with earlier reports suggesting a variety of neurobehavioral abnormalities and cognitive deficits after 3-NP administration (Kumar & Kumar, 2009b;Palfi et al, 1996). It has also been reported that 3-NP produces lesion in hippocampal CA1 and CA3 pyramidal neurons, areas of the brain associated with cognitive task (Sugino et al, 1999).…”
Section: Discussionsupporting
confidence: 93%
“…Primates given chronic low doses of MPTP (to mimic Parkinson's disease) or 3-NP (to mimic Huntington's disease) display profound cognitive and visual deficits prior to the development of gross motor impairments (see Schneider & Roeltgen, 1993;Roeltgen & Schneider, 1994;Schneider & Pope-Coleman, 1995;Palfi et al, 1996). These results, along with those from selective lesions of the sensorimotor and associative portions of the primate striatum (e.g., Divac et al, 1967;Miyachi et al, 1997), support the concept that basal ganglia systems contain separate motor and cognitive circuits.…”
Section: Clinical and Pathological Studiesmentioning
confidence: 78%
“…The Dl receptors are positively can be generated by dopamine autoxidation or through coupled to adenylyl cyclase, and phosphorylation of the action of monoamine oxidase, a mitochondrial encalcium channels by protein kinase A increases wholezyme (Graham eta!., 1978;Graham, 1984). Autoxidacell calcium currents and can consequently lead to a tion leads to production of hydroxyl and superoxide rise in intracellular Ca 2~concentration (Trautwein and radicals, hydrogen peroxide (which can form hydroxyl Hescheler, 1990;Hartzell et al, 1991). The D2 recepradicals in the presence of transition metals such as tors are negatively coupled to adenylyl cyclase, and iron), and quinones (Graham, 1984).…”
Section: Discussionmentioning
confidence: 99%